Exploring the intricacies of plant growth promoting rhizobacteria interactions: an omics review - Kamogelo Mmotla; Nompumelelo R. Sibanyoni; Farhahna Allie; Lungile Sitole; Thendo Mafuna; Manamele D. Mashabela; Msizi I. Mhlongo (Annals of Microbiology)
Abstract Background Plant growth-promoting rhizobacteria (PGPR) are beneficial microorganisms that inhabit the rhizosphere. PGPR play a role in stimulating plant growth and development and enhancing plant resistance and tolerance to biotic and abiotic stresses. To effectively fulfil their roles, PGPR engage in intricate interactions with one another, a phenomenon that occurs within the rhizosphere. Mainbody. This collaborative synergy among PGPR species within the rhizosphere is essential for them to perform their functions optimally. Nonetheless, the precise mechanisms and dynamics of PGPR-PGPR interactions, particularly at the transcriptomic level, remain the subject of ongoing research. Scientists are actively exploring and studying how these microorganisms interact and coordinate their activities within the rhizosphere, shedding light on the molecular processes underpinning their cooperative efforts. In this review, we undertake a thorough examination centred on the communication systems that regulate interactions among PGPR in the rhizosphere. Our examination delves into the mechanisms by which this communication triggers alterations at both the transcriptomic and metabolomic levels. Additionally, we assess the cutting-edge omics technologies currently available to study these intricate processes. Conclusion Understanding the modes of communication and molecular mechanisms underlying these interactions is crucial for harnessing their full potential, particularly in sustainable agriculture. By exploring transcriptomic and metabolomic alterations driven by these interactions, as well as the integration of advanced omics technologies, researchers can uncover new insights into decoding these complex processes, paving the way for innovative strategies to enhance sustainable agriculture.